New surgical technique for the correction of congenital muscular torticollis (wry neck) - L.F.A. Stassen, C.J. Kerawala (Blackwell Synergy, 2000)
The term torticollis means twisted neck (from the Latin ‘tortus’ – twisted and ‘collum’ – neck) and, although Alexander the Great had it in the third century BC,1 it was not until 1641 that Isaac Minius attempted the first surgical correction.